Robin Watkins' 5th Birthday Party at Home - Watkins, Howard::::::::: (1987)
Robin Watkins opening presents; Adam Watkins and friends looking on Dylan Tidyman-Jones in red, Art Wille with black cap, Rachel Roelke in green shirt/pink overalls; Happy Birthday Robin sign in background